Efektivitas Sosialisasi Tatap Muka Dalam Menangani Problematika Perceraian Pada Masyarakat Kurang Mampu - Bunga Pamela Anugraheni; Meisya Larasati Putri Hermawan; Dativa Wilma Azali; Nailah Hanna Sausan (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
This study investigates the increasing divorce rate in Indonesia, particularly among the poor, by identifying key factors and exploring the role of face-to-face legal socialization in addressing this issue. Using a descriptive qualitative approach, the research includes a case study of a female informant who experienced divorce. The findings indicate that divorce is not attributed to a single cause but results from a combination of factors, including incompatibility from the outset of the marriage, the husband's absence, economic instability, conflicts with extended family, and poor communication within the household. Furthermore, the study reveals that face-to-face legal socialization proves more effective in enhancing legal understanding and creating an open space for discussion, despite challenges such as limited access and community participation. The research emphasizes the need for a more empathetic and communicative approach in divorce prevention efforts, particularly at the grassroots level, to address the underlying issues contributing to divorce.